2009
DOI: 10.1007/s11745-009-3324-4
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Activates Some SREBP‐2 Targets Independent of Cholesterol and ER Stress in SW620 Colon Cancer Cells

Abstract: The SREBP-2 transcription factor is mainly activated by low cellular cholesterol levels. However, other factors may also cause SREBP-2 activation. We have previously demonstrated activation of SREBP-2 by the polyunsaturated fatty acid docosahexaenoic acid (DHA) in SW620 colon cancer cells. Despite activation of SREBP-2, only a few target genes were induced and cholesterol biosynthesis was reduced. In the present study, gene expression analysis at early time points verified the previously observed SREBP-2 targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(122 reference statements)
2
7
1
Order By: Relevance
“…It is unlikely however that ω3PUFAs interfere with this axis in HT29-dx cells: they indeed reduced HMGCoAR activity and protein in chemoresistant cells, but did not decrease the nuclear translocation of SREBP-2 and the transcription of HMGCoAR gene. Our data are partially in contrast with previous works showing that DHA activated SREBP-2 in SW620 colon cancer cells [23,24], without changing however the transcription of HMGCoAR [23]. As far as we know, these works were performed on colon cancer cells without a MDR phenotype; this may explain the different behavior of DHA in SW620 cells and in chemoresistant HT29-dx cells.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is unlikely however that ω3PUFAs interfere with this axis in HT29-dx cells: they indeed reduced HMGCoAR activity and protein in chemoresistant cells, but did not decrease the nuclear translocation of SREBP-2 and the transcription of HMGCoAR gene. Our data are partially in contrast with previous works showing that DHA activated SREBP-2 in SW620 colon cancer cells [23,24], without changing however the transcription of HMGCoAR [23]. As far as we know, these works were performed on colon cancer cells without a MDR phenotype; this may explain the different behavior of DHA in SW620 cells and in chemoresistant HT29-dx cells.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, this is the first work reporting that ω3PUFAs activate the E3 ligase Trc8. This observation also provides mechanistic insights to explain previous works, reporting that DHA increases the activity of ERAD system [23,24], and the proteasomal degradation of specific proteins in colon cancer [50]. Contrarily to DHA and EPA, AA had no effect on Trc8, in keeping with its inefficacy in reducing HMGCoAR and cholesterol synthesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar to our results, preadipocytes and mesenchymal stem cells treated with saturated PAL demonstrated multiple ER stress responses, evident by increased splicing of Xbp-1 mRNA [27, , 42]. Exposure of human colon cancer cells (SW620) to DHA (70 mM) has been shown to induce ER stress, as demonstrated by increased levels of phosphorylated eIF2α and the ER-localized PERK pathway [43]. The mechanism by which PAL or DHA induce cellular stress is still not clear.…”
Section: Discussionsupporting
confidence: 81%
“…Saturated lipids have been shown to induce cholesterol biosynthesis ( 27 ), while lipids rich in polyunsaturated fatty acids have been shown to reduce cholesterol biosynthesis in the liver ( 28 ). Moreover, in vitro experiments have previously demonstrated that the polyunsaturated fatty acid, DHA, activates SREBP2 without increasing cholesterol biosynthesis ( 29,30 ), suggesting that polyunsaturated fatty acids regulate cholesterol biosynthesis through alternative mechanisms.…”
Section: Discussionmentioning
confidence: 99%